2019
DOI: 10.1093/gastro/goz001
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab for chronic antibiotic-refractory pouchitis

Abstract: Background Chronic antibiotic-refractory pouchitis (CARP) is a complication of ileal pouch-anal anastomosis (IPAA), which poses a therapeutic challenge. Vedolizumab, a gut-selective monoclonal antibody to the α4β7 of integrin, has been used in such patients, but data on its efficacy are limited. Our aim was to assess the efficacy and safety of vedolizumab as induction therapy in CARP patients. Methods In this single-center, historic cohort, patients with CARP who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…As regards anti-TNF agents, there is clearly more benefit in CD-like complications of the pouch than in refractory pouchitis, highlighting the need to differentiate these two entities both in daily practice and clinical trials [181]. Recent studies suggest that vedolizumab is effective and can be safely used for chronic antibiotic refractory pouchitis patients [182][183][184]. Lastly, ustekinumab appears to be a safe and effective treatment for chronic pouchitis and CD of the pouch in biologic-naïve patients and those who failed anti-TNF or vedolizumab therapy [185].…”
Section: Item 23 a Combination Of Two Antibiotics Is Usually Effective In Chronic Pouchitis (El3) Alternative Treatments Include Oral Budmentioning
confidence: 99%
“…As regards anti-TNF agents, there is clearly more benefit in CD-like complications of the pouch than in refractory pouchitis, highlighting the need to differentiate these two entities both in daily practice and clinical trials [181]. Recent studies suggest that vedolizumab is effective and can be safely used for chronic antibiotic refractory pouchitis patients [182][183][184]. Lastly, ustekinumab appears to be a safe and effective treatment for chronic pouchitis and CD of the pouch in biologic-naïve patients and those who failed anti-TNF or vedolizumab therapy [185].…”
Section: Item 23 a Combination Of Two Antibiotics Is Usually Effective In Chronic Pouchitis (El3) Alternative Treatments Include Oral Budmentioning
confidence: 99%
“…Opinions were, however, split when it came to treatment strategies for patients who did not respond to optimized anti-TNFα. The continued inclusion of vedolizumab as a treatment option is supported by a number of recent studies [35][36][37][38]. Ustekinumab, which was voted for by 11% of experts, has been investigated in at least one study and was shown to lead to improvement of clinical and endoscopic endpoints [38].…”
Section: Figure 6 Treatment Algorithm For Moderately or Severely Active Ulcerative Colitismentioning
confidence: 99%
“…Multiple studies have evaluated the role of vedolizumab (VDZ) in the treatment of chronic pouchitis. 64 71 In a retrospective study of 20 patients with CADP or CARP, 55% of whom were anti-TNF experienced, the mean PDAI decreased from 10 to 3 ( p < 0.01) at week 14. Clinical response to VDZ was defined as a decrease in PDAI by 3 points, which was achieved in 64% of patients.…”
Section: Chronic Inflammatory Complications Of the Pouchmentioning
confidence: 99%